The Influence of Emotional Attachment and Previous Experience on Repurchase Intention Mediated by Customer Trust in Tokopedia (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to examine the influence of emotional attachment and previous experience on repurchase intention, both directly and through customer trust as a mediating variable. The research focused on Tokopedia users domiciled in Aceh, involving a sample of 203 respondents. Structural Equation Modeling (SEM) with the assistance of AMOS software was used as the analytical method. The results demonstrate that emotional attachment and previous experience exert a positive and significant influence on both customer trust and repurchase intention. Moreover, customer trust is found to have a significant impact on repurchase intention. A pivotal finding of this study is that customer trust significantly mediates the relationship between emotional attachment and previous experience with repurchase intention. These findings underscore the essential role of trust-building as a strategic lever for fostering customer loyalty within the context of e-commerce platforms. This research is expected to serve as a valuable reference for stakeholders in the digital industry in formulating customer relationship strategies grounded in experiential and emotional engagement